PFMIKIRAN HUKUM MUHAMMAD HASHIM KAMALI - ., Nurwahidah (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
the study on the subsiance oflstamic Law (al-Fiqh) should always be relaled to thc stud)r on the mthodology (ushul al-fiqh). Many has done srudy on it ircluding Muhammad Hashim Kamali. Muhammad Hasyim Kamati stated thar lhc A.abic writers tend to explajn the hisrorical developmenr of fiqh and ushul fiqh separately, and their w ting in ushul fiqh is didecated merely for ltre jlridical maLerial of ushul fiqh. Muhammad lasyim Kanali ;n his writing Ptihqnes af Islanic Jutisptudence (The Llanic Tects Society)oflets a crntn)ction of his law thought basd on ushul fiqh. His ideas actually are not dificrenl from those of the previous ulemas, only in develop;ng the methoCological liamework ushul fiqtl his thought combjnes th salaf and khalaf approach witch has been systematically, clearly, atrd weltrtassifeid. Meanwhile, h s ihougth in the substantial Islamic law is considered modm especia y in rhe lb n of modem lransacion.",